Restriction fragment length polymorphism of polymerase chain reaction products from vaccine and wild-type varicella-zoster virus isolates. - LaRussa, P (1992)
The nucleotide changes that result in two restriction endonuclease polymorphisms that differentiate wild-type varicella-zoster virus (VZV) from the vaccine strain were determined. Oligonucleotide primers that flank these sites were used to amplify the intervening sequences with the polymerase chain reaction to identify VZV DNA in clinical isolates. Restriction enzyme digestion of the amplification products distinguished vaccine and wild-type genomes from one another. This study confirms the feasibility of amplifying VZV sequences so that they may be detected in clinical specimens and provides a molecular epidemiological approach to strain identification of VZV in vesicular lesions.